Diabetes Mellitus y Embarazo - Lisson, Rosa (1995)
Diabetes mellitus is a chronic metabolic disease with absolute or relative blood insulin deficit that results in hyperglicemia and glycosuria, increase in protein and fat catabolism and tendency to ketoacidosis. During pregnancy carbohydrate metabolism is affecter by the fetus (who cosumes maternal glucose and aminoacids), placental hormones (IICS, estrogens, progesterone) and cortisol, all having antiinsulinic effects. Gestational diabetes occurs in 3 to 6 per cent of pregnancies and is associated to macrosomy, birth trauma, cesarean section, and neonatal hyperbilirrubinemia, hypocalcemia and hypoglicemia. Diabetes mellitus complicates 0.1 - 0.5% of pregnant women and increases the incidence of spontaneous abortionm pregnancy induced hypertension, hydramnios, intrauterine fetal growth retardation, macrosomu, malformations and perinatal mortality. With insulin discovery and modern management in pregnant diabetic women, maternal and perinatal mortality have improved considerably. In our country, glycemia one hour post ingestion of 50 to 75 g of glucose in women withrisk factor is being used, repeating detection and stress charge at 24 to 31 and 33 to 36 weeks. Pre natal control of diabetic pregnant women must be frequent, multidisciplinary, with balanced diet, physical activity stimulus, early detection of complications and frequent determination of fetal growth, malformations, well-being and maturity by ultrasound and surfactant. Oral hypoglicemic agents are not recommended. Hospitalize at 36 weeks in manifest diabetes, before if complications are present. Deliver at term, having in mind macrosomy. Regulate fertility due to the high reproductive risk. With careful monitoring of their metabolism, diabetic patients without vascular complications can use low-dose ovulation inhibitors to prevent prevent pregnancy.